Exposure to air pollution increases susceptibility to ulcerative colitis through epigenetic alterations in CXCR2 and MHC class III regionResearch in context - Jie Chen; Han Zhang; Tian Fu; Jianhui Zhao; Jan Krzysztof Nowak; Rahul Kalla; Judith Wellens; Shuai Yuan; Alexandra Noble; Nicholas T. Ventham; Malcolm G. Dunlop; Jonas Halfvarson; et al. (EBioMedicine)
Summary: Background: This study aims to confirm the associations of air pollution with ulcerative colitis (UC) and Crohn's disease (CD); to explore interactions with genetics and lifestyle; and to characterize potential epigenetic mechanisms. Methods: We identified over 450,000 individuals from the UK Biobank and investigated the relationship between air pollution and incident inflammatory bowel disease (IBD). Cox regression was utilized to calculate hazard ratios (HRs), while also exploring potential interactions with genetics and lifestyle factors. Additionally, we conducted epigenetic Mendelian randomization (MR) analyses to examine the association between air pollution-related DNA methylation and UC. Finally, our findings were validated through genome-wide DNA methylation analysis of UC, as well as co-localization and gene expression analyses. Findings: Higher exposures to NOx (HR = 1.20, 95% CI 1.05–1.38), NO2 (HR = 1.19, 95% CI = 1.03–1.36), PM2.5 (HR = 1.19, 95% CI = 1.05–1.36) and combined air pollution score (HR = 1.26, 95% CI = 1.11–1.45) were associated with incident UC but not CD. Interactions with genetic risk score and lifestyle were observed. In MR analysis, we found five and 22 methylated CpG sites related to PM2.5 and NO2 exposure to be significantly associated with UC. DNA methylation alterations at CXCR2 and sites within the MHC class III region, were validated in genome-wide DNA methylation analysis, co-localization analysis and analysis of colonic tissue. Interpretation: We report a potential causal association between air pollution and UC, modified by lifestyle and genetic influences. Biological pathways implicated include epigenetic alterations in key genetic loci, including CXCR2 and susceptible loci within MHC class III region. Funding: Xue Li was supported by the Natural Science Fund for Distinguished Young Scholars of Zhejiang Province (LR22H260001) and the National Nature Science Foundation of China (No. 82204019). ET was supported by the CRUK Career Development Fellowship (C31250/A22804) and the Research Foundation Flanders (FWO). JW was supported by Belgium by a PhD Fellowship strategic basic research (SB) grant (1S06023N). JKN was supported by the National Science Center, Poland (No. 2020/39/D/NZ5/02720). The IBD Character was supported by the European Union's Seventh Framework Programme [FP7] grant IBD Character (No. 2858546).